2017
DOI: 10.4103/ijmm.ijmm_16_164
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Enteric Parasitic Infections among HIV-infected Individuals and Its Relation to CD4 T-cell Counts with a Special Emphasis on Coccidian Parasites at a Tertiary Care Centre in South India

Abstract: Coccidian parasites continue to be the most common aetiological agent of diarrhoea among patients with HIV. The increasing trend of positivity of both cystoisosporiasis and cryptosporidiosis over the study period and the high positivity of cryptosporidiosis in patients with lower CD4+ T-cell counts are issues of serious concern. The findings call for the need for the early diagnosis of coccidian parasites and appropriate intervention among HIV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
2
12
1
1
Order By: Relevance
“…Several studies were performed in Brazil where high variations in prevalence were also reported (1.1–13.0%) (Sauda et al ., 1993; Cardoso et al ., 2011; Assis et al ., 2013, Barcelos et al ., 2018). In the Indian subcontinent, high prevalence levels have also been reported, ranging between 20.9 and 30.8% (Prasad et al ., 2000; Vignesh et al ., 2007; Kulkarni et al ., 2013; Swathirajan et al ., 2017), but also the prevalences in the same area varied from report to report (from 1.2 to 31%) (reviewed by Mohanty et al ., 2013). Analysis of 88 transplant recipients in India, revealed that 3 (3.4%) had the parasite (Yadav et al ., 2016).…”
Section: Distribution and Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies were performed in Brazil where high variations in prevalence were also reported (1.1–13.0%) (Sauda et al ., 1993; Cardoso et al ., 2011; Assis et al ., 2013, Barcelos et al ., 2018). In the Indian subcontinent, high prevalence levels have also been reported, ranging between 20.9 and 30.8% (Prasad et al ., 2000; Vignesh et al ., 2007; Kulkarni et al ., 2013; Swathirajan et al ., 2017), but also the prevalences in the same area varied from report to report (from 1.2 to 31%) (reviewed by Mohanty et al ., 2013). Analysis of 88 transplant recipients in India, revealed that 3 (3.4%) had the parasite (Yadav et al ., 2016).…”
Section: Distribution and Prevalencementioning
confidence: 99%
“…The prevalence of infection to C. belli is significantly higher in HIV-infected patients compared to HIV-negative patients in different geographical areas: 0% (0/81) in HIV-negative vs 9.9% (13/131) in HIV-positive individuals in Brazil (Sauda et al ., 1993); 0.4% (1/266) in HIV-negative patients vs 28% (18/65) in HIV-positive patients in India (Kulkarni et al ., 2013); 0% (0/164) in HIV-negative patients vs 12.2% (26/214) in HIV-positive patients in Ethiopia (Assefa et al ., 2009); and 2.9% (50/1722) in HIV-negative patients compared to 8.4% (28/334) in HIV-positive patients in Peru (Chincha et al ., 2009). In HIV-infected persons, C. belli prevalence rates varied from 0.4% to 28% (DeHovitz et al ., 1986; Ros et al ., 1987; Sauda et al ., 1993; Lagrange-Xélot et al ., 2008; Chincha et al ., 2009; Kulkarni et al ., 2013; Swathirajan et al ., 2017; Barcelos et al ., 2018; Casmo et al ., 2018) (Table 2).…”
Section: Distribution and Prevalencementioning
confidence: 99%
“…In our study, the prevalence of Cystoisospora belli infection was 20.29% which is very high compared to reports across various parts of India and the developing world, a study done by Swathirajan et al . [ 16 ] at Chennai, South India, shows the prevalence of C. belli to be 60.9%.…”
Section: Discussionmentioning
confidence: 99%
“…From patients' perspective, avoiding these infections relies on adhering to proper treatment regimens and maintaining good personal hygiene such as drinking boiled water, which may help in avoiding the risk of diarrheal disorders. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…Las infecciones por coccidios intestinales se encuentran ampliamente distribuidas en el mundo, detectándose tasas de prevalencias muy variadas: China (12%) 8 , Nepal (5,6%-14,1%) 9 , Polonia (5,4%) 10 , India (1,13-31,29%) 11,12 , Arabia Saudita (19,23%) 13 , Nigeria (2,2-32,2) 14 , Costa de Marfil (3,9-7,7%) 15 , Etiopía (7,9-20,8%) 16 , Libia (0.9-13%) 17 . Para países de Latinoamérica, se han encontrado cifras de prevalencia variables similares, incluyendo Guatemala (7,14-13,7%) 18 , México (9,,4%) 19,20 , Argentina (1,3%) 21 , Perú (4->40%) 22 .…”
Section: Introductionunclassified